Saikosaponin A Inhibits Triple-Negative Breast Cancer Growth and Metastasis Through Downregulation of CXCR4 - Wang, Ying; Zhao, Liang; Han, Xianghui; Wang, Yahui; Mi, Jinxia; Wang, Changhong; Sun, Duxin; Fu, Yunfei; Zhao, Xiaodong; Guo, Haidong; Wang, Qiangli (Frontiers in Oncology, 2020)
Purpose: Due to a lack of recognized molecular targets for therapy, patients with triple-negative breast cancer (TNBC), unlike other subtypes of breast cancers, generally have not benefited from the advances made with targeted agents. The CXCR4/ SDF-1 axis is involved in tumor growth and metastasis of TNBC. Therefore, down-regulation of the expression of CXCR4 in cancer cells is a potential therapeutic strategy for inhibiting primary tumor growth and metastasis of TNBC. In order to identify bioactive compounds that inhibit the expression of CXCR4 in traditional Chinese medicines, we investigated the capacity of saikosaponin A (SSA), one of active ingredients isolated from Radix bupleuri, to affect CXCR4 expression and function in TNBC cells. Methods: Analyses of cell growth, migration, invasion, and protein expression were performed. Knockdown by small interfering RNA (siRNA) and non-invasive bioluminescence were also used. Results: SSA reduced proliferation and colony formation of SUM149 and MDA-MB-231 cells. SSA inhibited migration and invasive of TNBC cells. For mice, SSA inhibited primary tumor growth and reduced lung metastasis of highly metastatic, triple-negative 4T1-luc cells. SSA inhibited CXCR4 expression, but did not regulate CXCR7 expression in vitro and in vivo. The inhibitory effects on the migration and invasive TNBC cells were reversed by down-regulation of CXCR4 expression. In addition, SSA inactivated the Akt/mTOR signaling pathway and inhibited MMP-9 and MMP-2 expression. Conclusions: The results show that SSA exerts an anti-TNBC effect through the inhibition of CXCR4 expression and thus has potential to be a candidate therapeutic agent for TNBC patients.